Bulleyaconitine A Inhibits Morphine-Induced Withdrawal Symptoms, Conditioned Place Preference, and Locomotor Sensitization Via Microglial Dynorphin A Expression - Zhao, Meng-Jing; Wang, Mi-Ya; Ma, Le; Ahmad, Khalil Ali; Wang, Yong-Xiang (Frontiers in Pharmacology, 2021)
Bulleyaconitine A (BAA), a C19-diterpenoid alkaloid, has been prescribed as a nonnarcotic analgesic to treat chronic pain over four decades in China. The present study investigated its inhibition in morphine-induced withdrawal symptoms, conditioned place preference (CPP) and locomotor sensitization, and then explored the underlying mechanisms of actions. Multiple daily injections of morphine but not BAA up to 300 μg/kg/day into mice evoked naloxone-induced withdrawal symptoms (i.e., shakes, jumps, genital licks, fecal excretion and body weight loss), CPP expression, and locomotor sensitization. Single subcutaneous BAA injection (30-300 μg/kg) dose-dependently and completely attenuated morphine-induced withdrawal symptoms, with ED50 values of 74.4 and 105.8 μg/kg in shakes and body weight loss, respectively. Subcutaneous BAA (300 μg/kg) also totally alleviated morphine-induced CPP acquisition and expression and locomotor sensitization. Furthermore, subcutaneous BAA injection also specifically stimulated dynorphin A expression in microglia but not astrocytes or neurons in nucleus accumbens (NAc) and hippocampal, measured for gene and protein expression and double immunofluorescence staining. In addition, subcutaneous BAA-inhibited morphine-induced withdrawal symptoms and CPP expression were totally blocked by the microglial metabolic inhibitor minocycline, dynorphin A antiserum, or specific KOR antagonist GNTI, given intracerebroventricularly. These results, for the first time, illustrate that BAA attenuates morphine-induced withdrawal symptoms, CPP expression, and locomotor sensitization by stimulation of microglial dynorphin A expression in the brain, suggesting that BAA may be a potential candidate for treatment of opioids-induced physical dependence and addiction.